The Formation of Carbon Management Accounting Systems: A Systematic Review of Driving Factors, Mechanisms, and Contextual Conditions - Putri, Yessica Mega; Artia, Wa Ode Tri; Fadilah, Erna Shaira; Shuyuan, Liu; Ramadhan, Yanuar (Dinasti Publisher, 2026)
This study analyzes the formation of carbon management accounting (CMA) systems through a systematic literature review focusing on driving factors, mechanisms, and contextual conditions. A PRISMA-based SLR yielded 21 final articles from Scopus (2020–2026) selected on the basis of direct conceptual relevance to CMA. Findings reveal that CMA system formation results from the simultaneous interaction of regulatory and internal organizational pressures, carbon information measurement and integration mechanisms, and contextual conditions encompassing industry characteristics, institutional maturity, and carbon financial risk exposure. This study advances theoretical integration within a domain that remains fragmented, offering an explicit multi-dimensional framework with particular implications for firms navigating mandatory sustainability reporting obligations in emerging economy contexts.